2010
DOI: 10.1016/j.nuclphysa.2010.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Cluster formation probability in the trans-tin and trans-lead nuclei

Abstract: Within our fission model, the Coulomb and proximity potential model (CPPM) cluster formation probabilities are calculated for different clusters ranging from carbon to silicon for the parents in the trans-tin and trans- lead regions. It is found that in trans-tin region the 12^C, 16^O, 20^Ne and 24^Mg clusters have maximum cluster formation probability and lowest half lives as compared to other clusters. In trans-lead region the 14^C, 18, 20^O, 23^F, 24,26^Ne, 28,30^Mg and 34^Si clusters have the maximum clust… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 69 publications
2
31
0
Order By: Relevance
“…Nevertheless, there are many recently published theoretical approaches on this topic, e.g., Refs. [13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, there are many recently published theoretical approaches on this topic, e.g., Refs. [13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Many theoretical models, both alpha decay like 11 and fission like, [12][13][14] have been proposed to explain CR phenomenon. Half-life values for different modes of cluster decays in both trans-tin region [14][15][16][17][18][19][20][21][22][23][24][25][26][27] and trans-lead 12 region have been calculated by using both alpha-like and fission-like theoretical models. These model based values are available in plenty in literature.…”
Section: Introductionmentioning
confidence: 99%
“…Santhosh et al, [7,8] have calculated half-lives for experimentally observed cluster decay modes of several heavy nuclei in the trans-lead and trans-tin region by using Coulomb proximity potential model (CPPM) [9,10]. The present work is an extension of our earlier work [11] which presents a comparative study of heavy particle decay using different nuclear potentials.…”
Section: Introductionmentioning
confidence: 85%